Asiyabad Özbek Ağzıyla Birkaç Nasrettin Hoca Fıkrası - Gültekin, Mevlüt (Gökkubbe, 2006)
Bu çalışmada Özbek Türkçesinin İranlılaşmış ağızlarına giren, Kuzey Afganistan'ın Asiyabad beldesinde konuşulan Özbek Türkçesi ağzından kaydedilmiş 7 Nasrettin Hoca fıkrası çevriyazı alfabesiyle verilmektedir. Metinler Türkiye Türkçesine aktarılmış, ses ve şekil bilgisi özellikleri verilmiş ve çalışmanın sonuna, metinlerde geçen bütün kelimeleri, metinlerdeki anlamlarıyla gösteren bir indeks konulmuştur. İndekste alıntı kelimelerin kökenleri de verilmiştir. This article consists of 7 transcribed texts of Nasreddin Hodsha's anecdotes, recorded in the dialect of the town Asiyabad, spoken in Northern-Afghanistan, which belongs to the Iranized dialects of Uzbek. The texts are translated into Turkish, phonological and morphological properties of the texts provided in the grammatical section. At the end ofthe work is placed a glossary containing all the words occuring in the texts, with the meaning in the context. The origins of foreign words are shown in the glossary, too.
Few Nasraddin Khoca Jokes with Asiyabad Uzbek Dialect
Keywords: Afganistan Özbek Türkçesi; Özbekçe; Türk Lehçeleri; Ağızbilim; Dilbilim; Afghano-Uzbek; Uzbek; Turkic Languages; Dialectology; Linguisticts